Solve for Z in J=H+(Z(I-H)), where H=E+(Z(F-E) & I=F+(Z(G-F)), where E=A+Z(B-A) & F=B+(Z(C-B)) & & G=C+Z(D-C)

Expert Answers

An illustration of the letter 'A' in a speech bubbles

To solve for Z you will need to begin by isolating any terms that have Z in them

Step 1: Begin with your original equation  J = H + (Z (I - H))

Step 2: Subtract H from each side of the equation: J - H = Z (I -...

Get
This Answer Now

Start your 48-hour free trial to unlock this answer and thousands more. Enjoy eNotes ad-free and cancel anytime.

Start your 48-Hour Free Trial

To solve for Z you will need to begin by isolating any terms that have Z in them

Step 1: Begin with your original equation  J = H + (Z (I - H))

Step 2: Subtract H from each side of the equation: J - H = Z (I - H)

Step 3: Divide each side of the equation by I - H: (J - H)/(I - H) = Z

All of the extra information is not needed to solve for Z.  When you are solving math problems, you always want to be certain to determine what is extra information & eliminate it.

I hope this helps.

Approved by eNotes Editorial Team